KEBIJAKAN CINA MEMBATASI EKSPOR MINERAL LOGAM TANAH JARANG (LTJ/RARE EARTH) KE AMERIKA SERIKAT TAHUN 2012 - Suryadi, Budi; Tjarsono, Idjang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research explains about China’s rare earths export restriction to United States in 2012. Rare earth minerals or rare earth elements is one of the unrenewable natural resources and became important components for high-tech products in 21st century’s life. China became a leader in rare earth industry and has control over 90 percent of global’s rare earths supply and production. However, Chinese Government start to restrict rare earths export and use this leverage as a economic instrument that affects the importer countries that depends on its supply, such as United States. The reasons behind export restriction was based on environmental problems, to fullfil increasing domestic demands and to sustain it’s unrenewable resources. The sources that is used on this research are obtained trought the books, journals, reports, documents, websites, online media, and also earlier related researches. This research use nation-state as the analysis level with international political economy, national interest and rational model concepts. This research is intended to assessing China’s rare earths policy implications to the United States’ high-tech products, economic, political, and national security situations. As the implications of this policy, United States worries about its domestic rare earth shortages could affect its national interest and sued Chinese Government to World Trade Organization due to unfair China’s export restriction and monopoly.Keywords : Rare Earths, Export Restriction Policy, China, United States, International Political Economy